ENVIRONMENTAL, SOCIAL AND GOVERNANCE DISCLOSURE AND FIRM PERFORMANCE OF LISTED ENTITIES IN SRI LANKA: A MIXED METHOD APPROACH - Nanayakkara, M. S. (Faculty of Graduate Studies, University of Kelaniya, Sri Lanka., 2023)
In the modern business landscape, transparency is a fundamental corporate value and a key driver of sustainability, necessitating ESG integration to reflect non-financial performance. Despite prior research, a consensus on the impact of ESG disclosure on firm performance in developing countries is lacking. This study fills the gap by examining ESG disclosure levels and their impact on firm performance using a mixed-method approach. The study selected 101 companies listed on the Colombo Stock Exchange from 2012/2013 to 2019/2020. The impact of ESG disclosure on firm performance is measured by Return on Assets (ROA), Return on Equity (ROE), and Tobin’s Q, employing panel data analysis techniques. To address endogeneity issues, the study uses System Generalized Method-of-Moments (System GMM) estimators. The study results show that ESG disclosure has no effect on the performance of listed companies in Sri Lanka. Factors identified in the thematic analysis encompass lack of awareness, inadequate integration into decision-making, disclosure quality, cost constraints, and institutional weaknesses. The level of ESG disclosure is influenced by awareness, lack of proper guidelines, absence of stakeholder demands, top management commitment, capture information, accounting education, and social, political, and economic context. This illustrates how isomorphic pressures, legitimacy considerations, and regulatory influences shape ESG disclosure practices. This study enriches the literature by expanding both theoretical and empirical insights into ESG reporting. The study provides valuable guidance for companies aiming to enhance performance through ESG implementation and disclosure, highlighting the importance of aligning Sri Lankan policies with global ESG standards.
Keywords: Corporate Governance; ESG Disclosure; Firm Performance; GRI Guidelines; Sustainability Reporting